PENGARUH PENGGUNAAN MEDIA SOSIAL DAN PEMANFAATAN MARKETPLACE TERHADAP ORIENTASI KEWIRAUSAHAAN SERTA IMPLIKASINYA PADA KESIAPAN BERWIRAUSAHA MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN ANGKATAN 2022 - Gultom, Nurani; Hasyim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the suboptimal utilization of social media and marketplaces as productive tools to support student entrepreneurship, despite both having great potential to improve entrepreneurial orientation and entrepreneurial readiness in the digital era. This study aims to analyze the influence of social media and marketplace use on entrepreneurial orientation and its implications for entrepreneurial readiness of Office Administration Education students, Class of 2022, State University of Medan. The study used a quantitative approach with a causal associative method. The study population consisted of 64 students, all of whom were sampled using a saturated sampling technique. Data collection was conducted through questionnaires, while data analysis used Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the assistance of the SmartPLS application. The results showed that social media use had a positive and significant effect on entrepreneurial orientation and entrepreneurial readiness. Marketplace use had a positive and significant effect on entrepreneurial readiness, but not a significant effect on entrepreneurial orientation. In addition, entrepreneurial orientation had a positive and significant effect on entrepreneurial readiness. The results of the mediation test indicate that entrepreneurial orientation mediates the influence of social media use on entrepreneurial readiness, but it is unable to mediate the influence of marketplace use on entrepreneurial readiness. These findings indicate that productive social media use plays a significant role in shaping entrepreneurial orientation and enhancing students' entrepreneurial readiness in the digital era.